An experimental study of relative humidity and air flow effects on positive and negative corona discharges in a corona-needle charger - Artit Yawootti (2018)
© 2015 Elsevier B.V. In this paper, the effects of inlet air RH and air flow rate on positive and negative corona discharges in a corona-needle charger have been experimentally studied and discussed. Its corona discharge characterizations in terms of current-to-voltage relationships of the corona-needle charger on the effects of inlet air RH and air flow rate were evaluated at applied corona voltages between 0 and 3.1 kV, an air flow rates between 5 and 15 L/min, a relative humidity between 20 and 90%, and an operating pressure of about 101.3 kPa. Experimental results were shown that discharge current is strongly affected by the RH level of the inlet air. The positive discharge current was found to be decreased with increasing RH value at RH values below 60% and increased with increasing RH value at RH value above 60% in the same corona voltage. The negative discharge current was found to be stable with increasing RH value at RH values below 40% and increased with increasing RH value at RH value above 40% in the same corona voltage. For the air flow rate effects, the positive discharge current was found to slightly decrease when the air flow rate increased at RH value below 90% and to increase with the air flow rate at RH value of 90%. For the negative corona, the discharge current was also found to monotonically decrease when the air flow rate increased.